Undergraduates of University of the West Indies - Jamaica, W. I. - The Novelty Trading Co. Ltd. (Kingston : The Novelty Trading Co., Ltd.)
Postcard shows a picture of six graduates in their gowns talking to each other on a lawn at the University of West Indies.
Level 1 deterioration.
Special Collections Floor
Keywords: The University of the West Indies, Mona (U.W.I.).; Universities and colleges; Undergraduates; St. Andrew -- Jamaica; Postcards